THE VIETNAM PIETA: SHAPING THE MEMORY OF SOUTH KOREA’S PARTICIPATION IN THE VIETNAM WAR - Guichard, Justine (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2019)
Conceived to commemorate the victims of South Korea’s participation in the Vietnam War, the statue of the Vietnam Pieta invites us to question who shapes the memory of this neglected facet of the conflict. The present article analyzes the various actors involved in this contentious process in and across both countries, starting with the South Korean activists behind the statue’s making and the movement for recognizing the crimes committed by their army. Examining these activists’ advocacy work since the late 1990s, the article argues that they are triply situated in the fight over remembering South Korea’s intervention in Vietnam. Truth advocates first appear in a position of privilege and leadership vis-à-vis Vietnamese victims of South Korean military wrongdoings, which raises the issue of the material and political asymmetries at stake in the construction of memory. Simultaneously, the same advocates occupy a position of marginality vis-à-vis the dominant public discourse held on the war by Hanoi and Seoul, whose common interest lies in deepening their mutually beneficial but unequal economic partnership. Thirdly, the memory of the conflict pits truth activists against another group within their own civil society: veterans’ organizations aggressively denying all war crimes accusations. Ultimately, remembering the war is not the object of a bilateral dispute between the South Korean and Vietnamese states, but rather a site of domestic tensions within South Korea itself.